Cooperative transportation of an object with a nonholonomic constraint by a swarm robot - Yuto Fukao; Tatsuro Terakawa; Takahiro Endo; Fumitoshi Matsuno; Yoshihiro Morimoto; Takumi Koshimoto; Daisuke Mizuno (ROBOMECH Journal)
Abstract In this paper, we propose a distributed controller for the cooperative transportation of an object with a nonholonomic constraint by a swarm robot. Because an object with passive wheels fixed to it does not slide along the axle direction, its velocity constraint is nonholonomic. We set the center of rotation of the object as a control point of the entire system. To derive the control point of an object with passive fixed wheels, we analyze dynamics of the object. Then we design a distributed cooperative transportation controller considering the nonholonomic constraint of an object with passive fixed wheels based on a kinematic model. We divide the distributed controller into two steps. In the first step, each robot derives the desired velocity and angular velocity of the object to achieve its desired position and orientation. In the second step, each robot calculates its desired velocity to achieve the object’s desired velocity and angular velocity. Each robot moves and pushes the object using the distributed controller, and can transport it to the desired position and orientation. We verify the effectiveness of the proposed controller in dynamic simulations and real robot experiments.